2015
DOI: 10.1146/annurev-physiol-021014-071727
|View full text |Cite
|
Sign up to set email alerts
|

Regeneration and Repair of the Exocrine Pancreas

Abstract: Pancreatitis is caused by inflammatory injury to the exocrine pancreas, from which both humans and animal models appear to recover via regeneration of digestive enzyme-producing acinar cells. This regenerative process involves transient phases of inflammation, metaplasia and redifferentiation, driven by cell-cell interactions between acinar cells, leukocytes and resident fibroblasts. The NFκB signaling pathway is a critical determinant of pancreatic inflammation and metaplasia, whereas a number of developmenta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
172
0
3

Year Published

2015
2015
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 162 publications
(184 citation statements)
references
References 117 publications
3
172
0
3
Order By: Relevance
“…Pancreatic injury also triggers a counteractive regenerative response that restores digestive enzyme-producing acinar cells. This response entails the proliferation of residual acinar tissue and acinar to ductal metaplasia (ADM), a process in which acinar cells dedifferentiate to become ductal progenitors, which eventually restore acinar tissue mass and function (35,36). Atg7 Δpan 12-wk-old pancreata exhibited up-regulation of several pancreatic progenitor and ductal markers, including Ptf1, Sox9, CK19, and Pdx1, as well as the Notch target genes Hes1 and Nestin (Fig.…”
Section: Loss Of Atg7 Results In Er Stress and Mitochondrial Dysfunctmentioning
confidence: 99%
“…Pancreatic injury also triggers a counteractive regenerative response that restores digestive enzyme-producing acinar cells. This response entails the proliferation of residual acinar tissue and acinar to ductal metaplasia (ADM), a process in which acinar cells dedifferentiate to become ductal progenitors, which eventually restore acinar tissue mass and function (35,36). Atg7 Δpan 12-wk-old pancreata exhibited up-regulation of several pancreatic progenitor and ductal markers, including Ptf1, Sox9, CK19, and Pdx1, as well as the Notch target genes Hes1 and Nestin (Fig.…”
Section: Loss Of Atg7 Results In Er Stress and Mitochondrial Dysfunctmentioning
confidence: 99%
“…Other authors have reported an association with ampullary adenocarcinoma and intraductal papillary mucinous neoplasm (IPMN) (6,26). There have also been reports of an increase in the size of the remnant pancreas and recurrent acute pancreatitis as a form of presentation (48).…”
Section: Discussionmentioning
confidence: 99%
“…In experimental models of acute pancreatitis and in partial resections of the pancreas, regeneration of the pancreas has been reported in mice and children with nesidioblastosis, but never in adults (41,48,49). In the regenerative response of the pancreas, the presence of acinar-ductal metaplasia has been reported where there is an upregulation of ductal markers such as CK19 and SOX9.…”
Section: Discussionmentioning
confidence: 99%
“…Ces limites ont réorienté les investigations vers des stratégies de différenciation in situ, sans recours à l'isolement et à la culture cellulaires. Au-delà de la controverse sur les capacités des cellules acinaires à produire spontanément de nouvelles cellules β lors de pancréatecto-mies ou autres lésions pancréatiques [42], il est admis que ces cellules sont capables de régénérer le pancréas exocrine [43]. Elles sont considérées à ce titre comme des progéniteurs facultatifs.…”
Section: Cellules Acinairesunclassified